2016
DOI: 10.1038/gim.2015.83
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of genotypes and parent of origin on cancer risk and age of cancer development in PMS2 mutation carriers

Abstract: A germ-line mutation in one of the mismatch repair (MMR) genes causes Lynch syndrome (LS), an autosomal dominant disorder characterized by the clustering of colorectal cancer (CRC) and endometrial cancer (EC) within affected families. Higher risks have been reported for other cancers such as ovarian and urothelial cell cancer. However, thus far only one study has confirmed these risks in PMS2 mutation carriers. 1The MMR proteins normally act together to repair mismatches that occur during cell replication. MSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…The established effect of genomic variants on RNA expression can also be used in genotype–phenotype correlation studies. RNA analysis results reported in this study contributed to a genotype–phenotype study of heterozygous pathogenic PMS2 variants found in European Lynch syndrome patients [Suerink et al., ].…”
Section: Discussionmentioning
confidence: 73%
“…The established effect of genomic variants on RNA expression can also be used in genotype–phenotype correlation studies. RNA analysis results reported in this study contributed to a genotype–phenotype study of heterozygous pathogenic PMS2 variants found in European Lynch syndrome patients [Suerink et al., ].…”
Section: Discussionmentioning
confidence: 73%
“…A second limitation might be that we did not correct for the specific mutation present in each family, mainly because in the majority of families the segregating PMS2 mutation is rare or even unique. A previous study by our group did not identify such a correlation with CRC risk in PMS2 carriers (Supplemental Tables 2a + 2b Table: for more details) [ 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, genotype-phenotype correlations in Lynch syndrome and CMMRD have been proposed (although thus far no conclusive evidence has been yielded and some studies even show contradictory results). [30][31][32][33][34][35] If correlations exist, variants with a milder phenotype might be overrepresented in a CMMRD cohort. For PMS2, age at cancer diagnosis and risk estimates were within the range of previous retrospective studies that corrected for ascertainment bias, indicating that we have not selected a cohort of (solely) low-risk PMS2 alleles.…”
Section: Discussionmentioning
confidence: 99%